The morphology of human rod ERGs obtained by silent substitution stimulation - Maguire, J.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Mckeefry, D. (Documenta Ophthalmologica, 2017)
To record transient ERGs from the light-adapted human retina using silent substitution stimuli which selectively reflect the activity of rod photoreceptors. We aim to describe the morphology of these waveforms and examine how they are affected by the use of less selective stimuli and by retinal pathology.Rod-isolating stimuli with square-wave temporal profiles (250/250 ms onset/offset) were presented using a 4 primary LED ganzfeld stimulator. Experiment 1: ERGs were recorded using a rod-isolating stimulus (63 ph Td, rod contrast, C rod = 0.25) from a group (n = 20) of normal trichromatic observers. Experiment 2: Rod ERGs were recorded from a group (n = 5) using a rod-isolating stimulus (C rod = 0.25) which varied in retinal illuminance from 40 to 10,000 ph Td. Experiment 3: ERGs were elicited using 2 kinds of non-isolating stimuli; (1) broadband and (2) rod-isolating stimuli which contained varying degrees of L- and M-cone excitation. Experiment 4: Rod ERGs were recorded from two patient groups with rod monochromacy (n = 3) and CSNB (type 1; n = 2).The rod-isolated ERGs elicited from normal subjects had a waveform with a positive onset component followed by a negative offset. Response amplitude was maximal at retinal illuminances <100 ph Td and was virtually abolished at 400 ph Td. The use of non-selective stimuli altered the ERG waveform eliciting more photopic-like ERG responses. Rod ERGs recorded from rod monochromats had similar features to those recorded from normal trichromats, in contrast to those recorded from participants with CSNB which had an electronegative appearance.Our results demonstrate that ERGs elicited by silent substitution stimuli can selectively reflect the operation of rod photoreceptors in the normal, light-adapted human retina.
EVALuna2:21335